2018
DOI: 10.1038/s41593-018-0278-y
|View full text |Cite
|
Sign up to set email alerts
|

Loss of neuronal network resilience precedes seizures and determines the ictogenic nature of interictal synaptic perturbations

Abstract: The mechanisms of seizure emergence, and the role of brief interictal epileptiform discharges (IEDs) in seizure generation are two of the most important unresolved issues in modern epilepsy research and clinical epileptology. Our study shows that the transition to seizure is not a sudden phenomenon, but a slow process characterized by the progressive loss of neuronal network resilience. From a dynamical perspective, the slow transition is governed by the principles of critical slowing, a robust natural phenome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
119
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 98 publications
(126 citation statements)
references
References 61 publications
6
119
0
1
Order By: Relevance
“…Moreover, algorithms that directly account for known seizure triggers, such as sleep-wake rhythms, as well as novel measurement approaches may offer alternative routes to performance gains. 2,3,16 In addition, recent work looking at long-term rhythms 18 holds significant promise for seizure forecasting, could be applied in the machine learning context, and suggests that the performance limits seen here may not be tied to potential limits imposed by the physiologic processes underlying seizure occurrence.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, algorithms that directly account for known seizure triggers, such as sleep-wake rhythms, as well as novel measurement approaches may offer alternative routes to performance gains. 2,3,16 In addition, recent work looking at long-term rhythms 18 holds significant promise for seizure forecasting, could be applied in the machine learning context, and suggests that the performance limits seen here may not be tied to potential limits imposed by the physiologic processes underlying seizure occurrence.…”
Section: Discussionmentioning
confidence: 97%
“…It is also very important to note that as a result of Kaggle contest formats, contestants did not have full timing information available to them for training, such as the time of interictal segments relative to preictal segments, which may significantly limit algorithm performance. Moreover, algorithms that directly account for known seizure triggers, such as sleep‐wake rhythms, as well as novel measurement approaches may offer alternative routes to performance gains . In addition, recent work looking at long‐term rhythms holds significant promise for seizure forecasting, could be applied in the machine learning context, and suggests that the performance limits seen here may not be tied to potential limits imposed by the physiologic processes underlying seizure occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…45 Here, we focused on the mechanism of seizure evolution dynamics after generation rather than seizure emergence. Chang et al found that the transition from interictal to seizure is modulated by interictal epileptiform discharges, which produce phasic changes in the slow transition process and exert opposing effects on the dynamics of a seizure-generating network, causing either antiseizure or proseizure effects.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence support the possibility that seizure onset has much in common with interictal spikes. First, EEG and ECoG recordings show that many partial and generalized seizures initiate with a single or recurrent spikes . Second, long‐term recordings reveal the frequency of interictal spikes tend to gradually increase prior to seizures .…”
Section: Discussionmentioning
confidence: 99%
“…First, EEG and ECoG recordings show that many partial and generalized seizures initiate with a single or recurrent spikes. 4,8,[44][45][46][47] Second, long-term recordings reveal the frequency of interictal spikes tend to gradually increase prior to seizures. 48 Third, single cell intracellular voltage recordings show that paroxysmal depolarization shifts underlie both spikes and onset of seizures.…”
mentioning
confidence: 99%